(untitled) (Revista Apotheke, 2020)
This article was born from a visit to the International Center of Photography (ICP) in New York, where the authors had the opportunity to talk with Fred Ritchin, ICP’s emeritus rector, and discuss the complete seminal text three decades in 2020 and the unexplored of Photography. Today, the fact that today we flood daily with images and that, at the same time, our ability to process or understand any meaning must be changed and not improved by that amount is a paradox. Thirty years ago, “In Our Own Image” by Ritchin was released. The book impressively described many of the ways in which an era of society’s digital transformation. When a second edition of the book was published in 1999, many of Ritchin’s changes, such as the embellishment of images by the computer and the weakening of the role of photography as a reliable witness, were already a reality.